Modeling the Impact of Non-Tariff Barriers in Services on Intra-African Trade: Global Trade Analysis Project Model - (:unkn) unknown (My University, 2022)
In 2015, the African Union launched negotiations to establish an African free trade agreement named AfCFTA (African Continental Free Trade Area). This paper examines the effects of the AfCFTA on intra-African trade in the short and long term. Associated with the implementation of this trade agreement, this paper assesses the impact of a reduction of 90% in import tariffs and 50% in non-tariff barriers (NTBs) for goods and services on GDP and intra-African trade. In this study, we highlighted the role of services in intra-African trade. We use the computable general equilibrium model (GTAP) and ad valorem equivalents (AVEs) of NTBs in services calculated using the Services Trade Restrictiveness Indices (STRIs) from the World Bank database following the Australian Productivity Commission’s methodology. Our results suggest that liberalization of services stimulates GDP growth in the long run. The reduction of NTBs in services leads to a rise in intra-African exports of agricultural products, manufactured goods, processed food, fuel, energy-intensive products, wood and paper products, textiles and clothing in the long run. The manufacturing and natural resources sectors are the most affected by the reduction of barriers to services trade in Africa. Moreover, this trade agreement creates both long-term trade creationand diversion.
Keywords: African Research